Gastrointestinal digestates of Grana Padano and Trentingrana cheeses promote intestinal calcium uptake and extracellular bone matrix formation in vitro. (November 2016) - De Luca, Paola; Bruschi, Sara; Maggioni, Margherita; Stuknytė, Milda; Cattaneo, Stefano; Bottani, Michela; Fiorilli, Amelia; Rossi, Filippo; De Noni, Ivano; Ferraretto, Anita
Abstract: In the present work, Grana Padano (GP) and Trentingrana (TN) cheeses at different ripening time were in vitro digested. To study calcium uptake and utilization, the intact digestates (selected doses that do not alter cell viability and Transepithelial Electrical Resistance) were administered to Caco2/HT-29 70/30 cells, cultured on a semipermeable membrane in transwells, as a model of human intestinal epithelium. Intact digestates as well as the whole basolateral solutions (mimicking the passage of digestates through intestinal cells before reaching the blood flow and bone) in parallel were further administered to human osteoblast-like cells SaOS-2 to study the extracellular bone matrix formation. In vitro digestates deriving from GP and TN promoted calcium uptake and extracellular bone matrix formation independently of both the cheese type and its ripening period (13, 19 or 26 months). The present study reports the ability of whole digestates of GP and TN cheeses to improve intestinal calcium absorption and bone matrix formation in vitro . Once fully explored at bone level, this finding could better support the role of cheese in ameliorating calcium deficiencies and associated diseases in vivo . Graphical abstract: Highlights: In vitro cheese digestates were used for calcium uptake and utilization studies. Digestates promoted calcium uptake and extracellular bone matrix formation in vitro . The reported digestate effects did not depend on cheese type and ripening time.